1984
DOI: 10.1002/j.2050-0416.1984.tb04228.x
|View full text |Cite
|
Sign up to set email alerts
|

Tanning Properties of Flavanols in Barley and Hops Measured by Reaction With Cinchonine Sulphate in Relation to Haze Formation in Beer

Abstract: The flavanoid polyphenol extracts from barley and hops were each separated into six fractions by adsorption chromatography on Sephadex LH20. These fractions were further characterised by several analytical methods, including high-performance liquid chromatography and a colorimetric measurement of polymerisation index. The tanning powers of the fractions were graded according to their reactivities with cinchonine sulphate solution in a standardised turbidometric test. Whereas, almost 75% of the flavanols from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…As an alternative to sample pretreatment, the use of more specific detection with the electrochemical detector was preferred. The amounts of monomeric and dimeric flavanols measured were similar to those reported by others (7,18,26,30,31,32) and the significance of such low concentrations (1-5 mg/L) in beer is in their effects on colloidal stability (2,7,8,17,22,24,35,37,40). Whereas it is certain that such small amounts of dimeric flavanols in beer can considerably increase the rate of chill haze formation, it seems that much larger concentrations of catechins may be required to exert the same destabilizing effect (2,7,8,22,37).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As an alternative to sample pretreatment, the use of more specific detection with the electrochemical detector was preferred. The amounts of monomeric and dimeric flavanols measured were similar to those reported by others (7,18,26,30,31,32) and the significance of such low concentrations (1-5 mg/L) in beer is in their effects on colloidal stability (2,7,8,17,22,24,35,37,40). Whereas it is certain that such small amounts of dimeric flavanols in beer can considerably increase the rate of chill haze formation, it seems that much larger concentrations of catechins may be required to exert the same destabilizing effect (2,7,8,22,37).…”
Section: Discussionsupporting
confidence: 86%
“…For several years it has been known that PVPP adsorbs from beer a complex mixture of phenolic substances and nitrogenous constituents (24). Our analyses of unstabilized beer showed that the only simple flavanoid constituents were prodelphinidin B3, procyanidin B3, catechin, and epicatechin.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In order to remove humulones, 1 g of ground hop pellets was ®rst extracted three times with 7 ml diethyl ether (super purity solvent, Romil, Loughborough, England) by shaking for 15 min and sonicating for 5 min (McMurrough & Hennigan, 1984). After centrifugation (3500 g, 10 min), the supernatant was removed.…”
Section: Polyphenol And¯avanoid Quanti®cation In Methanolic Hop Extractsmentioning
confidence: 99%
“…For stabilization Protesal at 0.05 g/L was used. Test A was conducted under the same conditions as Control A with the use of stabilizing agents such as Polyclar AT (an insoluble, high-molecular weight, cross-linked form of polyvinylpolypyrrolidone) which is reported to remove phenolic impurities (Helin 1980;Siebert et al 1981;McMurrough and Hennigan 1984). PVPP was used at 0.2 g/L and silica hydrogel at 0.5 g/L.…”
Section: Methodsmentioning
confidence: 99%